Implementation of Small Groups for Spiritual Development and Values Formation among Students in a Private School - Deloy, Zion Joyce Gloriana; Bausa, Kyla Kaye; Reofrir, Maricar; Glo, John Arvin (DAS Institute, 2025)
This research implemented small groups in the spiritual development and values formation of Grade 6 students at Unida Christian Colleges. The research examined its efficacy and aimed to fill a research gap in children’s spirituality by acknowledging the Grade 6 students' critical developmental phase and the significance of molding their spirituality and moral values. Employing the principles of Transformative Learning Theory, a four-week small group program was implemented, involving the students in conversations and tasks focused on their spiritual development and values formation that are relevant to their day-to-day lives. The results revealed a significant improvement in the students' perspectives on spiritual development and values formation following engagement in small group activities. By conducting a qualitative analysis, various themes such as spiritual growth through shared experiences, positive class relationships, practical application of biblical teachings, and strengthened faith were recognized, highlighting the transformative influence of small groups. The findings highlight the effectiveness of small group interventions in fostering spirituality, building positive peer connections, and instilling core values for holistic development among Grade 6 students. This study provides valuable insights for educators, policymakers, and Christian educational institutions, advocating for the implementation of small group activities in academic frameworks to promote students' spiritual and moral well-being.